Era no tempo do coronel... "eu não concordo muito com isso não!": arqueologia pública e interpretações colaborativas sobre a "Fazenda São Victor", Piauí - Vieira, Bruno Vitor de Farias (2017)
"Public Archeology" is one of the ever-growing segments since its inception in the mid-1970s. Since then, it has become part of debates, alternating debates on the social role of the archaeologist, preservation of sites, Insertion of society in scientific works and the future of this science / discipline. Throughout contradictions regarding the definition of its "public", the theorists of this segment have emphasized that "all Archeology, regardless of its thematic clipping or theoretical-methodological choices, should be, in essence, public" (CARVALHO, FUNARI, 2007). Thus, from the understanding of an archeology of the state: the "defender of the patrimony" and the "representative of society", to Archeology of "people, the public and the public" (idem). It is connected to this discussion the insertion of the context of the Archeology of Slavery in the southeast of Piauí and how these relations, at present, composse the memory and local history about this quotidian of the past and its resonance in the present. Following these reflections, this research aims to present a study under the bias of Collaborative Archeology, with the inhabitants of the community of Lagoa de São Vitor, located in the southeast of Piauí, in the identification and characterization of the constituent spaces of the former "Complexo Produtivo Fazenda São Victor". The results comprised the localization of six social spaces between the various actors who settled there: the headquarters, the corral, the slave quarters, the lagoon, the slave graveyard and the village of freed slaves, these places were characterized by from the interpretation of science and popular wisdom of the community, built on collaborative relationships of mutual respect.